ANALISIS PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI PERUSAHAAN (Studi Pada Perusahaan Consumer Goods Industry yang Terdaftar di BEI Tahun 2017-2019) - Agung Maulana Erick Ghifari Samosir; Paulus Th. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of corporate governance on the company's accounting conservatism as assessed from board of commissioner size, board of commissioner independency, board of commissioner expertise, and big 4 auditor reputation. The population in this study are consumer goods industry companies listed on the Indonesia Stock Exchange in 2017-2019. The sample in this study was selected by purposive sampling method. In this study there will be 33 companies that have met the criteria to be used as research samples. The method used in conducting the analysis is multiple linear analysis. The results of the research conducted indicate that the board of commissioner size and expertise do not have a significant effect on accounting conservatism in the consumer goods industry companies in Indonesia. Meanwhile, the board of commissioner independency and big 4 auditor reputation have a significant effect on accounting conservatism in consumer goods industry companies in Indonesia.